Dose Assessment and Considerations When a Radioactive Seed is Unrecoverable in a Breast Surgical Patient. Issue 3 (November 2016) - Harvey, Richard P.
Abstract : Abstract: Excision of non-palpable breast tumors in cancer patients has been routinely performed using surgical clips and wires placed under mammographic or ultrasound guidance. An alternative method exists for performing these surgeries without surgical wires and this approach has become more widely used at Oncology Centers in the United States. Roswell Park Cancer Institute (RPCI) performs many of their breast surgeries with radioactive seeds and has enjoyed favorable outcomes along with an enhanced patient experience. There are some inherent difficulties with using radioactive seeds, and seed tracking can be a problem during surgical procedures. When a seed is misplaced, an extensive search is conducted in an effort to locate the misplaced seed. Every attempt to recover these radioactive seeds should be made unless patient safety is jeopardized. If the seed is unrecoverable, then a dose assessment must be performed and corrective action determined. It is important to have adequate policies and procedures in place to prevent these rare occurrences. They should be treated as a radioactive medical event.